Studi Struktur Serat Agave Menggunakan Fourier Transform Infrared Spectroscopy - Fita Widiyatun; Neng Nenden Mulyaningsih; Nurfidah Dwitiyanti (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2019)
Agave plants are ornamental plants that generally grow wild in the yard or empty land. Apart from being an ornamental plant, agave plants have many uses and benefits. The use of agave plants is located on the plant fibers. One of the benefits of agave fiber is the material used to make a composite material for applications in the medical or industrial fields. The purpose of this study was to determine the fiber characteristics of agave plants including the crystallinity and regularity of agave fibers by testing using Fourier Transform Infrared (FTIR) Spectroscopy. Characterization with FTIR can be obtained information of C-O stretching cellulose 1 and sesulose 2 groups, C-H aromatic groups, C = C stretching aromatic ring (G) groups, C = C stretching aromatic ring (S) groups and OH groups from Agave fibers. Agave fibers are made in two different types of samples. The first sample is pure fiber without treatment called (UT) and the second sample, namely fiber with soaking sodium hydroxide (NaOH) is called treatment fiber (T). The results obtained show that T fibers have a degree of crystallinity and strength based on higher OH groups compared to UT fibers.